2016
DOI: 10.1111/nph.14382
|View full text |Cite
|
Sign up to set email alerts
|

Water supply and demand remain coordinated during breakdown of the global scaling relationship between leaf size and major vein density

Abstract: Vein networks that disobey the global scaling of major vein density with leaf size shed light on functional constraints of vein network formation in dicotyledons. Understanding their evolution, distribution and impact on vein-stomata-climate associations is an important contribution to our global view of vein network organization. Based on vein traits of 55 species of pantropical Ochnaceae, stomata and climatic niche data, and a dated molecular phylogeny, we unveil major structural shifts in vein networks thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…traits. Indeed, for more than two decades studies have suggested that the relationships among plant traits may be visualized as a network or correlogram, and sometimes analyzed using path analysis or structural equation models [21,26,[37][38][39][40][41][42][43]. Recent studies [40,44] have quantified parameters to describe the network topology and the interdependency of traits.…”
Section: Theoretical Basis For Plant Trait Network and Their Numeroumentioning
confidence: 99%
“…traits. Indeed, for more than two decades studies have suggested that the relationships among plant traits may be visualized as a network or correlogram, and sometimes analyzed using path analysis or structural equation models [21,26,[37][38][39][40][41][42][43]. Recent studies [40,44] have quantified parameters to describe the network topology and the interdependency of traits.…”
Section: Theoretical Basis For Plant Trait Network and Their Numeroumentioning
confidence: 99%
“…The coordination of stomatal and vein development has been described as the balance between water demand and supply in leaves (Brodribb & Jordan, 2011;Schneider et al, 2017).…”
Section: Stomatal Development Plasticity In Trees Via Different Mechamentioning
confidence: 99%
“…The occurrence of both rainforest and savanna species in several speciose genera in the Neo‐ and Palaeotropics also makes the family an excellent system for the study of biome transitions, particularly in light of recent efforts to address responses of rain forests to climate change and of climatic tipping points for rain forests (Hirota & al., 2011; Flores & al., 2017). The family is also very interesting with regard to the evolution of dioecy, andromonoecy and androdioecy (Schneider & al., 2002; Schneider & Zizka, 2016, 2017) and the evolution of unique leaf venation networks (Schneider & al., 2017). The lack of information on phylogeny and monophyly of the up to now recognized major groups has also been an impediment to taxonomic progress.…”
Section: Introductionmentioning
confidence: 99%